2014
DOI: 10.1099/vir.0.064220-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular mechanisms underlying potyvirus infection

Abstract: Potyviruses represent one of the most economically important and widely distributed groups of plant viruses. Despite considerable progress towards understanding the cellular and molecular basis of their pathogenicity, many questions remain about the mechanisms by which potyviruses suppress host defences and create an optimal intracellular environment for viral translation, replication, assembly and spread. The review focuses on the multifunctional roles of potyviral proteins and their interplay with various ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
120
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(131 citation statements)
references
References 168 publications
(251 reference statements)
1
120
0
10
Order By: Relevance
“…One of them is the small nuclear inclusion protein, NIa. Despite of its involvement in viral replication on the surface of the cytoplasmic membranes, this protein accumulates predominantly in the nucleus of infected cells (Ivanov et al, 2014). The elicitor of Ry-mediated resistance is presumably NIa, a proteinase, which interact directly or indirectly with the Ry protein and initiate a primary response leading to ER by preventing virus accumulation at an early stage of infection.…”
Section: Genes Associated With Er Type Resistancementioning
confidence: 99%
See 3 more Smart Citations
“…One of them is the small nuclear inclusion protein, NIa. Despite of its involvement in viral replication on the surface of the cytoplasmic membranes, this protein accumulates predominantly in the nucleus of infected cells (Ivanov et al, 2014). The elicitor of Ry-mediated resistance is presumably NIa, a proteinase, which interact directly or indirectly with the Ry protein and initiate a primary response leading to ER by preventing virus accumulation at an early stage of infection.…”
Section: Genes Associated With Er Type Resistancementioning
confidence: 99%
“…These experiments showed that the potyvirus-induced changes are not as pronounced at the proteome level as they are at the transcriptome level. It was concluded that the potyvirus infection induces selective changes in the host gene expression rather than a complete shut-off of protein synthesis (Ivanov et al, 2014).…”
Section: Effects Of Viruses On Potato Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Potyvirus genome consists of a ssRNA+ of approximately 10,000 nucleotides (nt) encapsidated in long and flexuous virions Ivanov et al, 2014) (Figure 3A). The genome is covalently linked in its 5' end to the viral protein genome-linked (VPg) and in its 3' end is polyadenilated.…”
Section: A Potyvirus-based Expression Vector For Metabolic Engineeringmentioning
confidence: 99%